Semantic Contingency of Maternal Verbal Input Directed at Very Preterm and Full-Term Children - Salerni, Nicoletta; Suttora, Chiara (Frontiers in Psychology, 2022)
Several studies have testified to the importance of a responsive linguistic input for children’s language acquisition and development. In particular, maternal use of expansions, imitations, interpretations, and labels has been shown to promote both children's language comprehension and production. From this perspective, the present study examined the semantically contingent linguistic input addressed to very preterm children’s comparing it to that directed to full-term children observed during a semi-structured play session when the children were 24 months of age. The relationships between maternal contingent utterances and children’s communicative repertoires were also investigated. The main results showed that mothers of full-term children produced a higher proportion of semantically contingent utterances than those of very preterm children; moreover, this variable was associated with children's more advanced communicative-linguistic outcomes. Overall, this study supports the interdependence between mothers’ use of certain linguistic strategies and children’s communicative-linguistic repertoire, extending this evidence to children born very preterm and suggesting the importance of considering the semantic contingency aspect of CDS to support the communicative and linguistic development of these children.